THE EFFECT OF COMPENSATION, ENVIROMENTAL WORK AND ORGANIZATIONAL CULTURE TO THE EMPLOYEE PERFORMANCE OF CV. STAR NINE TRITUNGGAL BABAT - Aila Okta Nur Reina Safitri; Nurul Badriyah; Yohronur Efendi (Sean Institute, 2023)
This study aims to determine how much influence the effect of compensation, environmental work and organizational culture has on the employee performance of CV. Star Nine Trinity Tripe . This type of research is quantitative. The population of this research is all employees of CV. Star Nine Trinity Tripe , amounting to 60 people. In addition, based on the results of the study, it was found that: (1) In the t-test (partial) the compensation variable with tcount 2.294 > ttable 2.003. environmental work variable with tcount 3.588> ttable 2.003. organizational culture variable with tcount 2.560 < ttable 2.003 means that there is a partially significant effect between compensation, environmental work and organizational culture to the employee performance. (2) In the F (simultaneous) test, Fcount 48.406 while Ftable 2.76 means that there is a simultaneous significant influence to the employee performance of. (3) Test results Multiple regression analysis of the environmental work variable is the variable that has the most dominant influence than other variables on the employee performance of, because the environmental work value (X 2 ) = 0.379 is greater than the compensation value (X 1 ) = 0.325 and organizational culture (X 3 ) = 0.186.